Disturbances in Brain Physiology Due to Season Play: A Multi-Sport Study of Male and Female University Athletes - Churchill, Nathan W.; Hutchison, Michael G.; Graham, Simon J.; Schweizer, Tom A. (Frontiers in Physiology, 2021)
High-performance university athletes experience frequent exertion, resulting in disrupted biological homeostasis, but it is unclear to what extent brain physiology is affected. We examined whether athletes without overtraining symptoms show signs of increased neurophysiological stress over the course of a single athletic season, and whether the effects are modified by demographic factors of age, sex, concussion history and sport-related factors of contact exposure and season length. Fifty-three (53) university-level athletes were recruited from multiple male and female sports at a single institution and followed longitudinally from beginning of season to end of season and one month afterwards, with a subset followed up at the beginning of next season. Advanced magnetic resonance imaging (MRI) comprehensively assessed white matter diffusivity, cerebral blood flow (CBF) and brain activity, while overtraining symptoms were assessed with Hooper’s Index (HI). Although athletes did not report increased HI scores, they showed increased white matter diffusivity and decreased CBF at end of season and one month afterwards, with recovery at follow-up. Global brain activity was not altered though, highlighting the ability of the brain to adapt to exercise-related stressors. Male athletes had greater white matter diffusivity at end of season, but female athletes had greater declines in CBF at one month post-season. Post-season changes were not related to change in HI score, age, concussion history, contact exposure or length of athletic season. The brain shows substantial but reversible neurophysiological changes due to season play in the absence of overtraining symptoms, with effects that appear to be sex-dependent but otherwise insensitive to demographic variations. These findings provide new insights into the effects of training and competitive play on brain health.